2020
DOI: 10.1088/1757-899x/981/4/042021
|View full text |Cite
|
Sign up to set email alerts
|

The Influence Of Process Parameters On The Surface Roughness Of The 3d Printed Part In FDM Process

Abstract: 3D printing is a promising digital manufacturing technique that produces parts with layer by layer. The influence of process parameters is investigated for ABS material in fused deposition modelling (FDM). This work aimed to determine the surface roughness of 3d printed parts of the ABS material with varied parameters of infill height and infill density. The results of the test show that the, surface roughness is higher (11.6mm) at 20% infill density with 0.26mm infill layer height. Also, ABS material surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(11 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…Another issue could be the lack of quality of the extruded polymer, which affects the overall surface quality and causes higher dispersion in the dimensional features of the patterns. This is in concordance with some studies that report that increasing the layer heights causes a rise in surface roughness [26,30,31].…”
Section: Surface Topography and Roughness Of The Textured Surfacessupporting
confidence: 93%
“…Another issue could be the lack of quality of the extruded polymer, which affects the overall surface quality and causes higher dispersion in the dimensional features of the patterns. This is in concordance with some studies that report that increasing the layer heights causes a rise in surface roughness [26,30,31].…”
Section: Surface Topography and Roughness Of The Textured Surfacessupporting
confidence: 93%
“…What's more, average surface roughness values were measured as 6,3 µm, 5,8 µm and 5,1 µm respectively for the specimens manufactured with infill rates of 40%, 70% and 100%. Similar findings were also observed at other studies performed by Sammaiah et al [36] and Dey and Yodo [37].…”
Section: B Surface Roughness Evaluationssupporting
confidence: 92%
“…The surface unevenness value of the upper layer of PCABS objects is calculated, and the mean average of surface roughness (Ra) and the mean maximum profile height (Rz) for each bio-inspired skeleton are provided in Figure a,b. As per shown in Figure c for the 2D roughness profiles, it is observed that the roughness profile is higher if the peak-to-valley difference is height, which is described by the nacreous sheet; however, it progressively declines for columnar nacre and a neat sample . The new PCABS component comprises an R A value (arithmetic average) of 2.02 μm and an R Z value of 14.336 μm; nonetheless, for the NC structure, a maximum R A reaches 11.038 μm, and a value of R Z observed as 49.408 μm and the highest surface roughness R A of 20.842 μm, and R Z of 103.959 μm are obtained for densely packed NC tablets.…”
Section: Resultsmentioning
confidence: 61%